A GAN-BERT based decision making approach in peer review (Social network analysis and mining, 2024)
Peer review comments are feedback provided to editors and authors by subject matter experts in order to assess a research work’s qualities. Those remarks represent the opinions of reviewers regarding the caliber and correctness of the study. They must provide evidence to support the reviewer’s choice to accept or reject the submitted paper. This research suggests a GAN-BERT based method to analyze the reviewers’ sentiment from their comments and automatically produce an unbiased and objective final evaluation about the acceptance or the rejection of the manuscript. Experimental findings show that our suggested approach is effective.